Public transport trends in Australia during the COVID-19 pandemic: An investigation of the influence of bio-security concerns on trip behaviour. (October 2021) - Beck, Matthew J.; Hensher, David A.; Nelson, John D.
Abstract: This paper draws on findings from an Australia-wide survey with data collected in three waves throughout 2020 to explore the impact of COVID-19 on public transport trends in metropolitan areas of Australia. Following consideration of the public transport sector response to the pandemic and the emerging literature context, we explore three principal questions: (i) How has weekly travel composition changed across the waves? (ii) How has level of concern with using public transport changed over the course of the pandemic given new bio-security concerns? and (iii) How has attitudes to risk been associated with the changes in PT use? A key finding is that concerns over bio-security issues around public transport are enduring, that concern about hygiene is significantly negatively related to public transport use and that those with higher concern about the hygiene of public transport also held higher concern about COVID-19 at work. Even as COVID-19 restrictions are eased, both concern about crowds and hygiene have a significant and negative correlation with public transport use. Concluding remarks are offered on what might need to happen for public transport patronage to start returning. Highlights: New data on changing patterns of use and attitudes towards public transport, including biosecurity concern during COVID-19. We investigate how has weekly travel composition changed since March 2020 The level of biosecurity concern with using public transport over the course of the pandemic is documented. We identify the drivers for use of public transport over the course of the pandemic The implications for public transport operations and policy are set out.